Creating a Collaborative Trauma-Informed Interdisciplinary Citywide Victim Services Model Focused on Health Care for Survivors of Human Trafficking. (July 2022) - Jain, Juhi; Bennett, Mackenzie; Bailey, Mark D.; Liaou, Daniel; Kaltiso, Sheri-Ann O.; Greenbaum, Jordan; Williams, Kimberly; Gordon, Mollie R.; Torres, Melissa I. M.; Nguyen, Phuong T.; Coverdale, John H.; Williams, Victor; et al.
Although human trafficking is recognized as a public health issue, research on the health effects of human trafficking and best intervention practices is limited. We describe 2 citywide collaborative victim services models, the THRIVE (Trafficking, Healthcare, Resources, and Interdisciplinary Victim Services and Education) Clinic at the University of Miami and Jackson Health System in Miami, Florida, and the Greater Houston Area Pathways for Advocacy-based, Trauma-Informed Healthcare (PATH) Collaborative at Baylor College of Medicine, CommonSpirit Health, and San Jose Clinic in Houston, Texas, funded in part by the Office for Victims of Crime, which focus on trauma-informed health care delivery for victims of human trafficking. From June 2015 through September 2021, the THRIVE Clinic served 214 patients with an average age of 28.7 years at the time of their first visit. From October 2017 through September 2021, the PATH Collaborative received 560 suspected trafficking referrals, 400 of which screened positive for labor or sex trafficking. These models serve as a framework for replication of interdisciplinary practices to provide health care for this unique population and preliminary information about the strategies put in place to assist victims during their recovery. Key lessons include the importance of a citywide needs assessment, patient navigators, interdisciplinary care, and building community partnerships to ensure safe housing, transportation, identification, health insurance, vocation services, input from survivors, peer-to-peer mentorship, and medical–legal services. Further research is needed to understand the detrimental health effects of trafficking and the health care needs of victims. In addition, a need exists to develop optimal models of care for recovery and reintegration for this patient population and to address public health, legal, and medical policies to ensure access to and sustainability of comprehensive, trauma-informed, interdisciplinary victim services.